A study of Self-beliefs of High and Low Academic Achievement of EFL Master Students at the University "Frères Mentouri", Constantine1 - Sakraoui, Amel (Journal of Human Sciences, 2019)
This article aims at investigating the relationship between the self- beliefs that Master EFL learners hold in the specific domain of Language Sciences and their first-semester academic achievement in discourse analysis. To this end, an initial version of the Language Sciences Academic Self-Beliefs Survey was developed in order to inquire about the type of beliefs adopted by low achieving and high achieving students in one of the modules taught for Master 1 learners in English language sciences namely, discourse analysis. Findings have revealed, in spite of the moderately ‘reserved’ statistical results, subtle associations and thought-provoking implications regarding students’ self- beliefs in the module of discourse analysis in particular and in English language sciences in general